Ozonized 2-hydroxypropyl-β-cyclodextrins as novel materials with oxidative and bactericidal properties. (1st September 2022) - Haddad, Elsi; Pagès, Marielle; Violleau, Frédéric; Marsan, Olivier; Manero, Marie-Hélène; Richard, Romain; Torré, Jean-Philippe
Abstract: Ozonized (2-Hydroxypropyl)-β-cyclodextrins (Oz-HPbCDs) were produced by direct gas/solid reaction between gaseous ozone (O3 ) and solid HPbCD. The solid materials obtained were first characterized using physical and chemical methods and compared to the initial HPbCD. The main process parameters of the synthesis were studied independently to assess their effect on the oxidizing power of Oz-HPbCDs. The ability of the Oz-HPbCDs to retain their oxidative properties over time was evaluated, at different storage temperatures, for a period of at least two months. Lastly, aqueous solutions of HPbCD and Oz-HPbCD at different concentrations were contacted with bacterial strains of Escherichia coli and Streptococcus uberis to see whether these materials might have bactericidal properties. Since normal bacterial growth was noted with HPbCD, the antimicrobial efficiency of Oz-HPbCDs was clearly demonstrated on these two types of bacteria. Graphical abstract: Unlabelled Image